Endothelial dysfunction and vascular stiffness in women with previous pregnancy complicated by early or late pre‐eclampsia. (January 2017) - Orabona, R.; Sciatti, E.; Vizzardi, E.; Bonadei, I.; Valcamonico, A.; Metra, M.; Frusca, T.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 22–23 ABSTRACT: Objectives: Pre‐eclampsia (PE) is associated with an increased cardiovascular risk later in life. The persistence of endothelial dysfunction after delivery may represent the link between PE and cardiovascular disease. We aimed to evaluate endothelial function and arterial stiffness after delivery of pregnancy complicated by early‐onset (EO) or late‐onset (LO) PE and their correlation with gestational age and mean uterine artery pulsatility index at PE diagnosis and birth‐weight percentile. Methods: The study included 30 women with previous EO‐PE, 30 with previous LO‐PE and 30 controls with no previous PE. Participants were examined at between 6 months and 4 years after delivery. All included women were free from cardiovascular risk factors and drugs. Data on demographic and clinical characteristics during pregnancy were collected retrospectively from obstetrical charts. Endothelial function and arterial stiffness were assessed by peripheral arterial tonometry and pulse‐wave analysis. Results: All vascular parameters were significantly different, indicating circulatory impairment, in women with previous EO‐PE. Women with previous LO‐PE had higher vascular rigidity than did controls and all had normal values of reactive hyperemia index, although they were significantly lower when compared with those of controls. On multivariate analysis, gestational age and mean uterine artery pulsatility index at the time of PE diagnosis, and birth‐weight percentile were all statistically related to the vascular indices studied, after correcting for confounding parameters. Conclusions: Women with previous pregnancy complicated by PE, in particular those with early‐onset disease, showed persistent microcirculatory dysfunction, as suggested by a significant reduction in reactive hyperemia index value, and increased arterial stiffness. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.